Microbial stratification structure within cathodic biofilm of the microbial fuel cell using the freezing microtome method. (October 2017) - Li, Xiao; Lu, Yaobin; Luo, Haiping; Liu, Guangli; Zhang, Renduo
Graphical abstract: Highlights: The microbial stratification structure within cathodic biofilm of MFC was studied. Different bacterial communities were identified in different layers. Higher bacterial viability was observed within the top and bottom layers. Abstract: The aim of this study was to investigate the microbial stratification structure within cathodic biofilm of the microbial fuel cell (MFC) using the freezing microtome method. Experiments were conducted in a single-chamber air-cathode MFC with 0.8 g/L maltodextrin as substrate for ∼30 d operation. The maximum power density was 945 ± 10 mW/m 2 in the MFC. Maltodextrin resulted in the relative abundance of Candidatus Saccharibacteria of 37.0% in the anodic biofilm. Different bacterial communities were identified in different layers within the cathodic biofilm. The relative abundance of Enterococcus was 3.7%, 10.5%, and 1.6% in the top (100–150 μm), middle (50–100 μm), and bottom (0–50 μm) layers, respectively. Higher bacterial viability was observed within the top and bottom layers of the cathodic biofilm. Understanding the stratification of bacterial community in cathodic biofilm should be important to control the cathodic biofilm in the MFC.